Pengaruh Resilience at Work terhadap Job Satisfaction pada Karyawan PT. X - Muhammad Reza Indrasukma; Oki Mardiawan (UNISBA Press, 2024)
Abstract. The aim of this study is to find out how the influence of resilience at work on job satisfaction among PT. X employees. The theoretical concept used is Winwood's (2013) resilience at work which was redeveloped by Malik & Garg (2018) to explain the concept of Resilience at work, and Spector's (1997) job satisfaction theory to explain the concept of job satisfaction. The method used is non-experimental quantitative research using a cross-sectional study with a total of 122 respondents. The measuring tools used are Job Satisfaction Survey Spector (1997) and the Resilience at Work Malik & Garg (2018) measuring tool which was adapted into Indonesian by Muiz in 2018. The data analysis technique used was multiple regression analysis. Based on the results of the hypothesis test, it was found that there was no significant influence of work resilience on job satisfaction, namely 9.60%. Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pengaruh resilience at work terhadap job satisfaction pada karyawan PT.X. Konsep teori yang digunakan yaitu resilience at work Winwood (2013) yang dikembangkan kembali oleh Malik & Garg (2018) untuk menjelaskan konsep resilience at work, dan teori job satisfaction Spector (1997) untuk menjelaskan konsep job satisfaction. Metode yang digunakan adalah penelitian ini adalah kuantitatif non-eksperimental dengan menggunakan studi cross sectional dengan jumlah responden 122 orang. Alat Ukur yang digunakan Job Satisfaction Survey Spector (1997) dan alat ukur Resilience at Work Malik & Garg (2018) yang sudah di adaptasi kedalam Bahasa Indonesia oleh Muiz pada tahun 2018. Teknik analisis data yang digunakan adalah analisis regresi berganda. Berdasarkan hasil uji hipotesis didapatkan bahwa tidak terdapat pengaruh yang signifikan resilience at work terhadap job satisfaction yaitu sebesar 9,60%.